Analisis Streamlines Udara Di Sepanjang Permukaan Bodi Kendaraan Menggunakan Simulasi ANSYS Fluent - Robert, Rivaldo Anderson; Sucipta, Made; Widiyarta, I Made (Teknik Desain Mekanika; Vol 13 No 1 (2024): Januari 2024 : Teknik Desain Mekanika, 2024)
Abstract The vehicle body is one of the important parts of the vehicle that needs development, with the aim of making the vehicle body more aerodynamic. Many vehicle simulation studies have been conducted to analyze vehicle aerodynamic factors such as drag force, lift force, pressure gradient, and airflow, but the discussion of the streamlines phenomenon that occurs is still lacking. Therefore, in this study, simulating a vehicle body design using Ansys Fluent which will then analyze the streamlines that occur at several points along the vehicle body. This research also uses vehicle speed variations of 30 km/h, 40 km/h and 50 km/h to see the effect of vehicle speed on air streamlines that occur. The results showed that the airflow passing through the surface of the vehicle body will follow the shape of the vehicle body surface. However, at some points that have large angular curvature changes, the air flow is difficult to follow. What is also obtained is the occurrence of a wake or air vortex at the rear of the vehicle due to the separation of the flow at the trailing edge of the vehicle. And the increase in vehicle speed will also increase the air velocity gradient passing through the contour of the vehicle body surface. Keywords: Streamlines, Vehicle Body, Vehicle Speed, Aerodynamics